Peripheral Artery Disease and Continuous Flow Left Ventricle Assist Device: An Engaging Complement Analysis May Help to Guide Treatment. Issue 7 (13th February 2018) - Falletta, Calogero; Pasta, Salvatore; Raffa, Giuseppe Maria; Crinò, Francesca; Sciacca, Sergio; Clemenza, Francesco
Abstract: Use of continuous flow left ventricle assist device (CF‐LVAD) in advanced heart failure (HF) patients results in clinically relevant improvements in survival, functional capacity, and quality of life. Peripheral artery disease (PAD) can occur in patients with CF‐LVAD due to the high rate of concomitance between risk factors for atherosclerosis and HF. Diagnosis of PAD can be difficult in the specific setting of a patient supported by this kind of device because of the marked alteration in waveform morphology and velocity created by the artificial physiology of an LVAD. We report the case of a 53‐year‐old man with HF secondary to ischemic cardiomyopathy supported by the HeartWare HVAD as bridge to transplant, who after the implant developed symptoms suggestive of PAD. We describe additional computational flow analysis for the study of PAD‐related hemodynamic disturbances induced by a CF‐LVAD. Flow simulations enhance the information of clinical image data, and may have an application in clinical investigations of the risk of hemodynamic disturbances induced by LVAD implantation.